2021
DOI: 10.3389/fsoil.2021.630851
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms Underlying Nutrient Interaction of Compost and Mineral Fertilizer Application in Maize (Zea mays L.) Cropping System in Ghana

Abstract: Mechanisms underlying interactive effects of nutrient inputs on crop yields are poorly understood especially throughout sub-Saharan Africa. This research thus sought to evaluate the possible mechanisms causing the interaction effects from compost and mineral fertilizer and quantify the relative contribution(s) of the mechanisms to added benefits in grain yield. The research involved a 3-year field experiment followed by a greenhouse incubation study. Both field and incubation experiments were 5 × 5 factorial a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
0
1
0
Order By: Relevance
“…The lower true NUE trend observed in FW and GW compost treatments could also be attributed to the priming effect of compost on indigenous soil N mineralization, which in turn enhances the immobilization of fertilizer N and leads to lower fertilizer N uptake (Jenkinson et al., 1985). Positive N priming effects and temporary N immobilization have been attributed to synergistic and antagonistic interactions between composts and mineral fertilizers (Essel et al., 2021). Studies reported that compost application causes high immobilization of urea‐N, resulting in lower fertilizer N uptake efficiency in a corn system (Choi et al., 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The lower true NUE trend observed in FW and GW compost treatments could also be attributed to the priming effect of compost on indigenous soil N mineralization, which in turn enhances the immobilization of fertilizer N and leads to lower fertilizer N uptake (Jenkinson et al., 1985). Positive N priming effects and temporary N immobilization have been attributed to synergistic and antagonistic interactions between composts and mineral fertilizers (Essel et al., 2021). Studies reported that compost application causes high immobilization of urea‐N, resulting in lower fertilizer N uptake efficiency in a corn system (Choi et al., 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The combined application of manure and chemical fertiliser also increased SOC and N content associated with all aggregate fractions, compared to +m (Figure 2B,C), indicating that the mineral fertiliser is more beneficial for SOC sequestration when applied in combination with manure. Such findings were explained by the lower priming effect causing a reduction in SOC decomposition rate in +s+m due to the abundance of nutrients, mainly dissolved N, compared to +m (Abdalla et al., 2022; Essel et al., 2021). The higher soil N abundance limits the soil microbial need for soil organic matter mining for nutrients, thus reducing the decomposition rate and promoting C stabilisation (Chen et al., 2022).…”
Section: Discussionmentioning
confidence: 99%